Key insights into recent advances and challenges in COVID-19 management - Prakash Monika; Anushka A. Poola; Prithvi S. Prabhu; K. Samrat; C. Likhitha (Discover Public Health)
Abstract SARS-CoV-2 infection, commonly called COVID-19, has taken a jump from being rarely talked about to becoming a household name. Making it to history as the 5th global pandemic, this public health crisis has taken millions of lives all over the world. Right from the identification of patient zero, the pandemic has unfolded in waves of infection, triggering a domino effect that has impacted all aspects of life. Global efforts have been underway to combat this pandemic and minimize its repercussions, resulting in the development of efficient vaccines and drugs to treat the disease and control the spread of infection. However, making the benefits of these efforts available to everyone and walking the path towards the end of the pandemic remains a challenge. Keeping this in view, this review intends to present a summary of the sequential development of the pandemic, the recent advancements in the field of diagnostics and treatment, and the challenges that continue to remain in overcoming this public health crisis. It can be understood that the task of controlling and managing the impact of such a massive pandemic goes well beyond the boundaries of what present-day technology and advancements in the field of medicine and health care can offer. A collaborative and integrative approach between academic, scientific, social, and economic factors, along with close supervision and reinforcement of the current public safety protocols, can help to ensure a better management strategy to control the progression of COVID-19. Graphical Abstract